The self-replicating internet machine : exploring contextual shifts through the process of aggregation in new media channels - Effendy Muhammad Ibrahim (2012)
In times of rampant technological growth and information explosion, the role and influence of visual communication practice has been questioned. The democratization of media has blurred the traditional boundaries between producers and consumers, and has affected the practice of visual communication. This thesis investigates the state of the contemporary information culture as seen through the lens of new media and social media channels, when observing content-based aggregated platforms. It addresses these platforms and positions them as a collection of visual and cultural artifacts of our time. This investigative approach looks into the process of aggregation as well as the reproduction models of images and information; and how these phenomena affect contextual shifts in meaning.